TEACHING HISTORY AS AN OBJECT OF PEDAGOGICAL RESEARCH - Arslan Nafasov (The Bioscan, 2024)
This article discusses the importance of pedagogical technologies in history teaching and their use in the educational process. In particular, history teaching occupies an important place in the educational program, it serves not only as a storehouse of human experience, but also as an important tool for the formation of educated and active citizens. The importance of history education goes beyond simply memorizing past events and includes critical thinking, understanding complex social dynamics, and cultivating a sense of identity and continuity. In addition, history teaching is full of several conceptual problems, and teachers must make regular efforts to provide effective and meaningful education.